Anticipated and Repeated Shocks in Liquid Markets - Lou, Dong; Yan, Hongjun; Zhang, Jinfan (Review of Financial Studies, 2013)
[We show that Treasury security prices in the secondary market decrease significantly in the few days before Treasury auctions and recover shortly thereafter, even though the time and amount of each auction are announced in advance. These results are linked to dealers' limited risk-bearing capacity and end-investors' imperfect capital mobility, highlighting the important role of frictions even in very liquid financial markets. Our results imply a hidden issuance cost to the U.S. Department of the Treasury, estimated to be 9 to 18 bps of the auction size, or over half a billion dollars for the issuance size in 2007.]